Educational Needs Assessment of Health Educator Teachers from the Perspective of Themselves and School Administrators in Kouhdasht - Tayyebeh Asadi Malek Abadi; Mahmood Abolghasemi; Mahboobeh Arefi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Education is one of the strategic actions for human resources development. The purpose of education is improvement in functional outcomes and the knowledge, skills and attitude of staff. Appropriateness of organizational training and needs of employees predisposes improvement in potential capacity of employees and effectiveness and improvement of the performance of employees. The Purpose of this study was to explore the educational needs assessment of health educator teachers of Kouhdasht city from the perspective of administrators and themselves health educators. Materials and Methods: In this descriptive-applied study all health educator teachers and administrators in high schools (primary and secondary) in Koohdasht, Lorestan, Iran participated. The sample size consisted of 70 subjects (26 men and 44 women). Data were collected through the questionnaire that was based on Likert scale. Through task analysis, knowledge, skills and attitude of educators were extracted and examined validity and reliability of the questionnaire proved to be satisfactory. Descriptive methods, one sample T-test, independent T-test, Friedman test and analysis of variance were used for analysis. Results: Prioritize educational needs of health educator teachers from the perspective of themselves were life skills education, sex education (to girls/boys) and common infectious diseases in adolescents. From the perspective of school administrators, these priorities were Knowledge of pharmaceutical information and their side effects, methods of prevention of drug abuse among adolescents and life skills education. Conclusion: Results of study showed significant differences between the existing and desired level of knowledge, skill and attitude of health educator teachers. Consideration the educational needs of employees and their involvement in the assessment process will be helpful.